Cumulative atherosclerosis index of plasma exposure and new-onset diabetes in middle-aged and older adults: a prospective cohort analysis from the China Health and Retirement Longitudinal Study - Li, Yu; Gu, Rong; Chen, Li; Zhao, Qi; Wang, Yue (Frontiers in Nutrition, 2025)
IntroductionChina bears the world's largest diabetes burden (116 million adults). The Cumulative Atherosclerosis Index of Plasma (CumAIP), reflecting lipid-driven atherogenicity, may contribute to diabetes pathogenesis. This study investigates longitudinal associations between cumulative CumAIP exposure and diabetes incidence in middle-aged and older Chinese adults.MethodUsing data from the China Health and Retirement Longitudinal Study (CHARLS), we analyzed 10,395 diabetes-free participants at baseline (2011) with follow-ups in 2013, 2015, and 2018. Multivariable logistic regression adjusted for sociodemographic (age, gender, education), lifestyle (smoking, alcohol, sleep, physical activity), and clinical factors (systolic and diastolic blood pressure, BMI, waist circumference). Restricted cubic splines assessed dose-response relationships.ResultOver 7 years, 793 participants (15.73%) developed diabetes. The highest CumAIP quartile (Q4) had a 3.43-fold elevated diabetes risk vs. Q1 (OR = 3.82, 95% CI: 3.13–4.67). A linear dose-response relationship was observed (p for nonlinearity=0.44); each interquartile increase in CumAIP above 1.03 elevated risk by 90% (OR = 1.90, 95% CI: 1.75–2.07). CumAIP predicted diabetes moderately (AUC=0.64, cutoff = 1.03).ConclusionCumulative CumAIP exposure independently predicts diabetes incidence in middle-to-older adults, highlighting its potential for clinical risk stratification.